PEMBINAAN PRESTASI SEPAK BOLA DI SEKOLAH SEPAK BOLA (SSB) TUGU MUDA KOTA SEMARANG TAHUN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study to determine the purpose of the establishment of SSB , organization , training programs , facilities and infrastructure , human resources , the role of parents and the community , funding , distribution athlete in SSB Tugu Muda Semarang in 2013. The approach in this study uses a qualitative descriptive approach. Instruments and methods of data collection by observation, interviews , and documentation. The results showed that the SSB Tugu Muda Semarang existing board of management of systematic organization , in carrying out organizational activities carried out by organizations that exist. Based on the results penilitian , the suggestion that the author can say is keep the existing guidance systems , maintain the achievements that have been achieved so that it can attract more new athletes anymore.